1942
DOI: 10.1042/bj0360692
|View full text |Cite
|
Sign up to set email alerts
|

The absorption and excretion of zinc

Abstract: Zinc is now recognized to be one of the physiological elements, since it is essential for the growth of rats, and forms part of the carbonic anhydrase system [Shohl, 1939; Keilin & Mann, 1940]. Many foodstuffs contain comparable amounts of Fe and Zn, and the two metals tend to vary together. Thus white flour, egg-white and fish are poor sources of both, whereas brown flour, egg-yolk and meat are the reverse. There are, however,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
1
5

Year Published

1957
1957
1982
1982

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(34 citation statements)
references
References 8 publications
7
21
1
5
Order By: Relevance
“…Our results were similar to those of Dauncey et al [11], and Cavell and Widdowson [12]. Like MacCance and Widdowson [13], we did not find any relationship between urinary Zn excretion and Zn intake. Also, we did not find a relationship between urinary Zn and N excretion.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results were similar to those of Dauncey et al [11], and Cavell and Widdowson [12]. Like MacCance and Widdowson [13], we did not find any relationship between urinary Zn excretion and Zn intake. Also, we did not find a relationship between urinary Zn and N excretion.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between fecal Zn and Zn intake with diets 1 and 2 was also found by MacCance and Widdowson [13], and Cavell and Widdowson [12], However, there is no relationship between ingested Zn and fecal Zn in our preterm infants fed diet 3; it was probably due to the low Zn intake. We did not find a relationship between Zn and N fecal in group 3 because of the small fecal N excretion with diet 3.…”
Section: Discussionsupporting
confidence: 81%
“…Most studies have found that the intestine is the primary route of zinc excretion (9,15). An important finding is that under the conditions of this study there was a correlation between zinc excretion and fecal dry solids output.…”
Section: Discussionsupporting
confidence: 56%
“…Others have reported urinary zinc excretion of 0.3 to 1 mg/day under various dietary conditions and zinc intake levels (9,15). We found urinary zinc output to be constant for an individual within a narrow range of diets, but to vary by two-fold among the group.…”
Section: Discussionsupporting
confidence: 49%
“…Published data on urinary zinc approximate our findings. In the urine of normal individuals McCance and Widdowson found an average of 0.3 mg. of zinc per day; they also found that neither oral nor parenteral administration of zinc increased its renal excretion, although proteinuria was accompanied by a sevenfold increase in zincuria (10 of urine (13).…”
Section: Part I Ofmentioning
confidence: 96%